Green washing and its’ consequences in green entrepreneurial thrust: a systematic review of literature - Pushpanathan, A.; Mathushan, P. (Eastern University, Sri Lanka, 2020)
In general, research on entrepreneurship thus far, has been intriguingly slight investigation into the motives and influences on green entrepreneurs. In the recent decades, green entrepreneurship is ubiquitous and a vitally important phenomenon from the perspective of green economic development. Further, investment on green economy creates opportunities to accelerate sustainable economic growth while pursuing the global standards. This epitomizes that firms encounter increased environmental and social challenges to survive. Despite, some firms intend to produce and market its products by engaging in unscrupulous acts (Greenwashing) as a result of the sudden environmental conscience. More so, greenwashing is an evolving problem highly relevant to lodging industry. The present study aims to explore the key issues, significance, and consequences of the greenwashing and green entrepreneurship in enhancing sustainable environmental consciousness. A wide range of databases were used to find out relevant articles. The articles published other than English were excluded. From a large corpus of reviewed literature, it has been found that, green washing rigorously affects the health of the consumers and ruins the environment holistically. Intriguingly, it has been reviled that most of the entrepreneurs have lack of understanding and mindfulness on the greenwashing, green entrepreneurship and the effect of greenwashing on sustainable entrepreneurship success and environmental sustainability. Needless to say, it is pivotal to embrace green innovation and practices to reap competitive advantage.
Keywords: Economic Development; Entrepreneur; Green Entrepreneurship; Green washing